2014
DOI: 10.1093/ntr/ntu033
|View full text |Cite
|
Sign up to set email alerts
|

Hostility and Cigarette Use: A Comparison Between Smokers and Nonsmokers in a Matched Sample of Adolescents

Abstract: We examined the association between hostility-a personality trait reflective of negativity and cynicism toward others-and smoking in adolescents by measuring (a) several subcomponents of hostility, and (b) facial emotion processing ability, which has been previously linked to hostility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
0
10
0
3
Order By: Relevance
“…In the clinics, impaired social cognition was reported in patients with a drinking history (Valmas et al, 2014). Tobacco smokers and abstinent marijuana smokers appear more prone to display aggressive behavior (Bernstein et al, 2014; Budney et al, 2001), which may compromise social relationships. In cocaine abstinent animals, we found no modification of direct social interaction, but a moderately decreased interest for the social stimulus in the three-chamber test.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinics, impaired social cognition was reported in patients with a drinking history (Valmas et al, 2014). Tobacco smokers and abstinent marijuana smokers appear more prone to display aggressive behavior (Bernstein et al, 2014; Budney et al, 2001), which may compromise social relationships. In cocaine abstinent animals, we found no modification of direct social interaction, but a moderately decreased interest for the social stimulus in the three-chamber test.…”
Section: Discussionmentioning
confidence: 99%
“…Hostility and low social support are associated with worse lifestyle behaviors, including smoking, poor diet, obesity, and alcoholism (Bernstein et al 2014;Stickley et al 2014). It has been reported that hostile individuals may also manifest diminished vagal modulation of heart function and increased platelet reactivity, while low social support is associated with activation of the autonomic nervous system (Rozanskiet al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest potential influences for adolescents’ psychosocial factors in relation to their alcohol or cigarette use. Hostility [ 11 ] and emotional distress [ 12 ] were identified characteristics of school-aged (between 10 and 19) smokers, while emotional distress preceded or was concurrent with the patterns of alcohol and tobacco use among adolescents, aged between 15 and 18 [ 13 ]. Social isolation was another identified characteristic linking to adolescent cigarette use [ 14 ].…”
Section: Introductionmentioning
confidence: 99%